Leading and recognizing public value - Hartley, Jean; Parker, Steven; Beashel, Jim (Public Administration)
This article examines the relationship between leadership and public value, which is particularly challenging in a context of explicit contest and conflict. The theoretical framework is illustrated through a case study of policing rural crime. The study reveals that the police worked with multiple and competing publics rather than a single homogeneous public, and that part of their leadership role was to create and convene a public space in which different voices and divergent views could be expressed. The study notes that research needs to pay attention to the loss and displacement of public value, not solely its creation and recognition. The need to convene multiple publics required the police to lead, as part of a leadership constellation, and with political astuteness. The findings have wider relevance for other public services, and for studies of leadership and public value at the intersection between the state and civil society. - Reproduced.
Keywords: Public values